Current events in rheumatology - Zimmermann-Górska, Irena (Przewodnik Lekarza/Guide for GPs, 2012)
Most important recommendations on diagnostics and treatment of rheumatic diseases proposed by the European League Against Rheumatism (EULAR) and American College of Rheumatology (ACR) as well as results of some prospective studies published in 2010/2011 are presented